Relevansi Poligami Terhadap Keharmonisan Rumah Tangga Persepektif Pemikiran M Syahrur - Rizky Irfani; Hawa Hidayatul Hikmiyah; Imam Syafi’i (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Islam prescribes marriage as a sacred and fundamental institution in human life, aiming to preserve dignity, lineage, and to build a harmonious (sakinah), loving (mawaddah), and compassionate (rahmah) family. In Islamic teachings, marriage can be conducted either monogamously or polygamously, with specific conditions. In Indonesia, polygamous practices are strictly regulated by various legal provisions, such as Law Number 1 of 1974 and the Compilation of Islamic Law. Nevertheless, polygamy remains a controversial issue in society, often carried out without fulfilling legal requirements, such as through unregistered (sirri) marriages. This phenomenon reflects a legal dualism between religious norms and state regulations. Furthermore, the social construction of polygamy shows that it is not merely a religious or legal issue, but also a product of social, cultural, economic dynamics, and the evolution of modern values. This study aims to explore how social construction shapes the perception and practice of polygamy and its implications for household harmony. Using a multidisciplinary approach, this study seeks to provide a comprehensive understanding of the relevance of polygamy in contemporary society and its impact on family structure and child welfare.